2013-01-13 21:59:09 -0600 | commented answer | implication Thank you. Yes you are right , it is my mistake. Mathematics gives False for that implication. |

2013-01-08 01:28:30 -0600 | asked a question | implication Hello ! I wish to know how implication works in sage. In mathematica "Implies[True, False]" gives true. In sage I wrote "true.implies(false)" it gives attribute error : "'bool' object has no attribute implies" May I know How I should use implies in sage ? Thanks. |

2013-01-07 00:09:30 -0600 | commented answer | Need to improve a function in sage which checks trueness of expressions in an example. Thanks for the opinion. Yes I am interesting in finding whether computer algebra system like sage could be useful for checking purpose. Again thanks. |

2013-01-05 12:24:36 -0600 | commented question | Need to improve a function in sage which checks trueness of expressions in an example. Actually I am using mathematical problems from secondary school or high school level and trying to develop a function in sage which can check whether consecutive expressions are logically true or not, and hence we can check whole example whether it is correct or not. |

2013-01-04 20:41:57 -0600 | commented question | Need to improve a function in sage which checks trueness of expressions in an example. Sorry for improper English. In the preceding post I wanted to know How 'or' works in sage. But I got answer and now I know that. In this post I said I really need comments and suggestions because I want to edit this function and want to make it more reliable. |

2013-01-04 03:55:37 -0600 | asked a question | Need to improve a function in sage which checks trueness of expressions in an example. Hello ! Here I have made a function in sage which checks equality between consecutive expressions in an example. This function takes a set of examples as an argument. I want to improve my function and I really need comments and suggestions for correcting this function. Two examples which I have used are as follows. Example 1: (1 - ((1 + sqrt(a))/(sqrt(a)- 1))) = (1 + ((1 + sqrt(a))/(-sqrt(a) + 1))) = (1 + ((1 + sqrt(a))* (1 + sqrt(a))/((-sqrt(a) + 1) * (sqrt(a) + 1)))) = (1 + ((1 + 2* sqrt(a) + a)/(1 - a))) = (1 + ((1+a + 2* sqrt(a) )/(1-a))) = (((1-a)/(1-a)) + ((1+a + 2* sqrt(a))/(1-a))) = (1-a+1+a+ 2*sqrt(a))/(1-a) = (2+2*sqrt(a))/(1-a) Example2: x^2 + 2*x -3 == 0 <=> x == (-2 + (2^2 -4 <=> x == (-2 + (4+12)^(1/2))/(2 <=> x == (-2 + (16)^(1/2))/(2 <=> x == (-2 + 4)/(2 <=> x == (2)/(2) or x == (-6)/(2) <=> x == 1 or x == -3 The Problem is , following function checks first example correctly but not second example. In the second example, final answer is x == 1 or x == -3 but even if I provide wrong answer x == -1 or x == -3 it gives true. I have already received explanation about how 'or' behaves. see here ---------------Function begins --------------- var('j,e,exprList,as1,i,lhs,rhs,r,r1,x') def ComExpr(a): e1 is first example containing two elements one is list of expressions and another is assumption. Same for e2. e1 = [[(1 - ((1 + sqrt(a))/(sqrt(a)- 1))) == (1 + ((1 + sqrt(a))/(-sqrt(a) + 1))), (1 + ((1 + sqrt(a))/(-sqrt(a) + 1))) == (1 + ((1 + sqrt(a))* (1 + sqrt(a))/((-sqrt(a) + 1) * (sqrt(a) + 1)))), (1 + ((1 + sqrt(a))* (1 + sqrt(a))/((-sqrt(a) + 1) * (sqrt(a) + 1)))) == (1 + ((1 + 2* sqrt(a) + a)/(1 - a))), (1 + ((1 + 2* sqrt(a) + a)/(1 - a))) == (1 + ((1+a + 2* sqrt(a) )/(1-a))), (1 + ((1+a + 2* sqrt(a) )/(1-a))) == (((1-a)/(1-a)) + ((1+a + 2* sqrt(a) )/(1-a))), (((1-a)/(1-a)) + ((1+a + 2* sqrt(a))/(1-a))) == (1-a+1+a+ 2*sqrt(a))/(1-a)], a > 1]; sage: ComExpr([e1]) 1 [[True, True, True, True, True]] e2=[[x^2 + 2 |

2013-01-04 02:37:40 -0600 | commented answer | Behavior of 'or' Thank you. |

2013-01-04 01:24:44 -0600 | commented answer | Express domain membership Thank you, answer is very useful to me. |

2013-01-04 01:24:13 -0600 | commented answer | Express domain membership Thank you very much. |

2013-01-04 01:21:45 -0600 | received badge | ● Editor (source) |

2013-01-04 01:21:04 -0600 | asked a question | Behavior of 'or' Hello ! Here I have observed something in sage. sage: (x == 1 or x == -3).full_simplify() x == -3 sage: (x == -1 or x == -3).full_simplify() x == -3 sage: (x == -1 or x == 3).full_simplify() x == 3 sage: (x == -1 or x == -3).full_simplify() x == -3 sage: (x == 1 or x == -3).full_simplify() x == -3 I wish to know that why sage replies with the second argument. It is very necessary for me to understand this behavior of sage. Many Thanks ! |

2013-01-02 00:25:18 -0600 | asked a question | Express domain membership Hello I am trying to write an expressing showing its membership in ZZ, RR, QQ. e.g In sage "assume(x in ZZ) "gives me error. If I want to show that the symbol x belongs to ZZ then how should I express it ? Best wishes |

2012-10-26 21:07:52 -0600 | received badge | ● Student (source) |

2012-10-26 10:10:36 -0600 | commented answer | Equivalence operator Thank you very much ! |

2012-10-26 10:10:16 -0600 | received badge | ● Supporter (source) |

2012-10-26 04:08:10 -0600 | asked a question | Equivalence operator Hi ! Here I have a small sage code. x = var('x'); assume(x>0); print([x>0] == [1==1]) Sage prints it as "False". In the above piece of code "[x>0] == [1==1]" is logically true as there is already an assumption, though it gives False. I wish to know How does comparison operator "==" works ? Specially when comparing two predicates ? Does there any other function exist for such comparison ? Best regards |

2012-10-26 02:14:34 -0600 | commented answer | Assumptions in sage I got it.. Thank you. I wish to understand something regarding following code. x = var('x'); assume(x>0); print([x>0] == [1==1]) Sage answers it as "False" In the above piece of code "[x>0] == [1==1]" is logically true but it is gives False. I wish to know How does comparison operator "==" works ? Specially when comparing two predicates ? Does there any other function exist for such comparison ? Best regards |

2012-10-25 10:04:20 -0600 | asked a question | Assumptions in sage Hello! I am a sage beginner and I wish to know that How sage handles assumptions ? My example is as follows. a= var('a'); solve((a-1)*x ==3, x); and sage solves and gives correct solution [x==(3 / (a - 1))]. But here how the assumption (a != 1) is handled ? Because solution is not defined for (a=1). Best regards Charmi |

Copyright Sage, 2010. Some rights reserved under creative commons license. Content on this site is licensed under a Creative Commons Attribution Share Alike 3.0 license.